Association of immune-related adverse events induced by nivolumab with a battery of autoantibodies. (1st January 2021) - Les, Iñigo; Martínez, Mireia; Narro, Alicia; Pérez, Inés; Sánchez, Cristina; Puntí, Laura; Anaut, Pilar; Eguiluz, Saioa; Herrera, Alberto; Domínguez, Severina
Abstract: Background: The aim of this study was to assess the diagnostic performance of an autoantibody battery in patients receiving immune checkpoint inhibitors who experienced immune-related adverse events (irAEs). Methods: We retrospectively analyzed several variables potentially related to irAEs, namely, demographic, clinical, and laboratory characteristics, including an autoantibody battery (antinuclear, anti-neutrophil cytoplasmic, anti-thyroid antibodies and rheumatoid factor). Results: Sixty-nine patients (48 men; 61.8 ± 10.9 years at baseline) diagnosed with stage-4 solid-organ cancer and treated with nivolumab were followed up for 12 ± 10.3 months. Thirty-two irAEs were detected in 26 patients (37.5%). Adverse events occurred more commonly in women (62% vs. 27%, p  = .006), and younger patients (irAEs: 58.1 ± 9.8, no irAEs: 64.1 ± 10.9 years, p  = .024). Autoantibody battery results were available for 26 patients and were more frequently positive in patients with irAEs (87% vs. 30%, p  = .009). The positive predictive value, negative predictive value, and diagnostic accuracy of the battery were 82.3%, 77.8%, and 80.8%, respectively. Among the 64 patients with an evaluable response, 23 (38.5%) experienced tumour progression, this being less frequent in patients with irAEs (19% vs. 48.5%, p  = .03). Overall survival was higher in patients developing irAEs (HR = 1.88, p  = .05). Conclusion: Positivity in a readily available autoantibody battery may be associated with the occurrence of irAEs. KEY MESSAGES: Positivity in an accessible and inexpensive autoantibody battery including antinuclear, anti-neutrophil cytoplasmic, anti-thyroid antibodies and rheumatoid factor may be associated with the occurrence of immune-related adverse events. Patients with cancer on immune checkpoint inhibitors experiencing immune-related adverse events showed a lower risk of progression and better overall survival than patients not experiencing this type of adverse effect.